Impacts of fertilizers coupled with improved seeds on rice profitability in Tanzania: evidence from the national sample census of agriculture 2019/20 - Kadigi, Ibrahim L.; Sieber, Stefan (Frontiers in Agronomy, 2025)
IntroductionClimate change poses a growing threat to food security in Tanzania, particularly among smallholder rice farmers who rely on rain-fed agriculture and have limited adaptive capacity. Identifying effective input strategies to enhance both profitability and resilience is crucial to securing rural livelihoods and achieving sustainable development goals. This study evaluates the potential of improved seed varieties and fertilizers (both organic and inorganic) as tools for boosting income and reducing vulnerability among rice farming households.MethodsWe utilized nationally representative data from the 2019/20 National Sample Census of Agriculture (NSCA), which encompassed 6,025 rice farms across diverse agroecological zones in Tanzania. A Risk Simulation Model (RSM) was employed to estimate farm income distributions under varying yield and market price conditions. Farmers were categorized by seed type (local vs. improved) and fertilizer use (none, organic, or inorganic). Income thresholds of TZS 2.0 million/ha (low) and TZS 4.0 million/ha (high) were used to benchmark profitability and vulnerability levels across regions. ResultsThe combination of improved seeds and inorganic fertilizers significantly enhanced farm profitability. In the Southern Highlands Zone (SHZ), 20% of farms exceeded the upper-income threshold of TZS 4.0 million/ha. In contrast, farmers using local seeds without fertilizer faced a high financial risk, with 78% earning less than TZS 2.0 million/ha nationally. Organic fertilizers offered modest gains; in Zanzibar, they reduced the probability of falling into the low-income category by 14%. However, regional disparities were substantial. Fertile soils in the SHZ amplified input returns, while constraints in the Eastern Zones (EZ) and Zanzibar, including saline soils, land fragmentation, and institutional limitations, restricted profitability, even among users of inorganic fertilizer, with 58% remaining below the income threshold. DiscussionThese findings underscore the importance of spatially targeted strategies. High-potential areas, such as SHZ, could benefit from scaling up access to improved inputs through subsidized programs, like digital vouchers. In low-performing regions like EZ and Zanzibar, integrated interventions are needed, including site-specific soil management, saline-tolerant seeds, infrastructure improvements, and access to credit. A dual policy approach, combining short-term subsidies with long-term resilience-building, is essential to advance food security and sustainable profitability, in line with SDG 2 (Zero Hunger).